Osnovne fonološke osobine govora Srba u Ravnim Kotarima (sela Donje Biljane i Lišane Tinjske) (Philologia, 2021)
The subject of this paper is an analysis of the basic phonological characteristics in the speech of Serbs from Ravni Kotari (in the region of Northern Dalmatia) considering villages Donje Biljane and Lišane Tinjske. That includes main characteristics of vowel, consonant and prosodic system, which also represents three major sections of the paper. The speech of Serbs in Ravni Kotari belongs to the East-Herzegovinian speech type and it has not been examined in Serbian dialectological practice before. This speech has four accents with well-preserved post-accent lengths and very consistent transfers of accent to the proclitics. Some of the most typical features of vowel and consonant system include different types of reductions and asimilations. The corpus is made of audio recordings of Serbian inhabitants from that area using the interview method. The aim of this paper is gaining insight and better understanding of current lingustic situation regarding the speech of Serbs in Ravni Kotari and presenting its characteristics that define its place in the East-Herzegovinian speech type, more precisely – in the northwestern branch of that type.
Keywords: dialectology; newstokavian ijekavian dialect; East-Herzegovinian speech type; vowelism; consonantism; prosody; Ravni Kotari; Donje Biljane; Lišane Tinjske